HISTOPATHOLOGICAL SPECTRUM OF THYROID LESIONS AT TERTIARY CARE HOSPITAL IN WESTERN RAJASTHAN - Goyal, Divya; Negi, S R; Sajid, Abdul; Ahuja, Paridhi (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of the study is to determine the proportion of different patterns (colloid goiter, colloid cyst, papillary carcinoma, etc.) of thyroid lesions among the patients who have undergone surgical treatment. Methods: This was prospective and retrospective study to be conducted on 100 thyroidectomy specimens received in 5-year period (2016–2020) in Department of Pathology in Dr. S.N. Medical College, Jodhpur. Results: Age ranged from 10 days to 85-year-old, Peak incidence of thyroid diseases was seen in the third to fifth decade, 78% non-neoplastic lesion, Adenomatous goiter was the most common non-neoplastic lesion (65%), Papillary carcinoma was the most common malignant lesion encountered. Conclusion: Although non-invasive techniques like aspiration cytology provide a diagnosis in most, the ultimate answer often rests with histopathological examination of thyroidectomies, which forms the mainstay for a definitive diagnosis. Thorough gross and microscopic evaluation of thyroidectomies is mandatory even for non-neoplastic lesions as they sometimes harbor neoplasms.